"Learning Cantonese will help us": Elementary school students' perceptions of dual language education. Issue 3 (3rd July 2018) - Leung, Genevieve; Uchikoshi, Yuuko; Tong, Rosina
ABSTRACT: Though Cantonese has been spoken in the United States since the 1880s, very little is known about the attitudes of younger Cantonese speakers and learners and their ideas about their bi/multilingual identities. We fill this gap by reporting findings from focus group interviews with 14 fourth and fifth graders attending a Cantonese-English DLI school. We asked participants to discuss their beliefs about bi/multilingualism, their experiences with the DLI program, and their future aspirations using Cantonese. Three main themes resulted from the focus groups: utilitarian and intrinsic ideologies, the need for contextualizing language learning, and their general perceptions about their schooling experiences and building communicative repertoires. Specifically, findings show that students were expressive in discussing languages as a resource, the role of Cantonese in Chinese American immigration history, and the tensions between Cantonese and other more "economically useful" languages like Mandarin. Our data call for heightened attention to young learners' language ideologies and the need to better understand the complex ways learners see themselves as bi/multilingual individuals and their various intrinsic and instrumental perceptions of language learning and use.